Effects of corporate governance and environmental disclosure on performance - Ng, Yen Hong (2017)
Shareholders are the owners of business, however, the shareholders are usually not decision-makers on day-to-day operational decisions. Thus, the separation of ownership and control has resulted possible conflict of interest between the shareholders (principal) and board of directors (agent). Corporate governance, hence, acts as a monitoring mechanism to reduce the conflict of interest between them. On the other hand, companies today, are not just being expected to provide shareholders with good financial returns. The companies are expected to “give back” to the society, by involving in sustainability activities. However, the real commitments from companies to perform in sustainable manners are questionable. Over the years, environmental disclosure quality remained low among Malaysian listed companies. This study applies agency theory, stakeholder theory and legitimacy theory in assessing the effects of corporate governance and environmental disclosure quality on financial performance. Many past researches focus on the effects of corporate governance on financial performance; effects of environmental disclosure quality on financial performance; and effects of corporate governance on environmental disclosure quality separately. This study also intend to extend the current models and evaluate the mediating effect of environmental disclosure quality in between corporate governance and financial performance. This study is carried out in Malaysia among companies in environmentally sensitive industry as the operations of environmentally sensitive industry is considered to be more detrimental to the environment. Data are extracted from companies’ annual reports over five years’ duration, namely year 2011 to 2015. The data collected is then being analysed using panel data analysis. Results show non-duality of CEO significantly improve companies’ return on asset. Besides, the proportion of independent directors and non-duality of CEO are significant in improving the environmental disclosure quality of Malaysian listed companies. However, the environmental disclosure quality does not have significant influence towards companies’ financial performance. Lastly, environmental disclosure quality is an insignificant mediator between corporate governance and financial performance. This study provides empirical evidence to policymakers as to the importance of authority’s interference in bringing corporate governance and environmental disclosure quality to greater heights. Stricter regulatory requirements may be a necessity by regulators in order to further strengthen the corporate governance and environmental disclosure quality among Malaysian companies.